Research on the Application of Big Data Technology in Comprehensive Budget Performance Management - Xu, Xiaoman (International Journal of Global Economics and Management, 2024)
Since the 19th National Congress of the Communist Party of China first proposed the comprehensive implementation of budget performance management, building a comprehensive, all-encompassing, and fully integrated budget performance management system has become a key focus of the Chinese government. In recent years, big data technology has advanced rapidly and found wide application across various sectors of society. The question of how to effectively apply big data technology to comprehensive budget performance management has emerged as a central concern for the government. This paper, based on the practical application of big data technology in China’s budget performance management, explores issues currently present in budget performance management practices, focusing on areas such as performance indicator systems, database platform construction, evaluation management, and the application of results. Furthermore, it analyzes the application practices of big data technology in budget performance management abroad, providing insights into the implications for China’s own practices.